2016
DOI: 10.1001/jamapsychiatry.2016.2794
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Alterations of White Matter Developmental Trajectories in Infants With Prenatal Exposure to Methamphetamine and Tobacco

Abstract: Prenatal methamphetamine/tobacco exposure may lead to delays in motor development, with less coherent fibers and less myelination in SCR and PCR only in male infants, but these abnormalities may normalize by ages 3 to 4 months after cessation of stimulant exposure. In contrast, persistently less coherent ACR fibers were observed in methamphetamine/tobacco- and tobacco-exposed girls, possibly from increased dendritic branching or spine density due to epigenetic influences. Persistently lower diffusivity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 66 publications
5
57
1
3
Order By: Relevance
“…Methamphetamine is known to cross the fetal blood–brain barrier, leading to the accumulation of dopamine in synapses via reuptake blockade, and damage of neural terminals and synapses in offspring (Jablonski, Williams, & Vorhees, ; Jeng, Wong, Ting‐A‐Kee, & Wells, ). Brain imaging studies have found that prenatal methamphetamine exposure (PME) is associated with structural and functional alterations of striatal, frontal, parietal, and limbic regions in children, as well as changes to structural connectivity of such regions in infants (Chang et al, ; Kwiatkowski, Roos, Stein, Thomas, & Donald, ; Warton, Meintjes, et al, ; Warton, Taylor, et al, ). These regions underlie learning ability, sensorimotor, and executive function, as well as behavioral and emotional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Methamphetamine is known to cross the fetal blood–brain barrier, leading to the accumulation of dopamine in synapses via reuptake blockade, and damage of neural terminals and synapses in offspring (Jablonski, Williams, & Vorhees, ; Jeng, Wong, Ting‐A‐Kee, & Wells, ). Brain imaging studies have found that prenatal methamphetamine exposure (PME) is associated with structural and functional alterations of striatal, frontal, parietal, and limbic regions in children, as well as changes to structural connectivity of such regions in infants (Chang et al, ; Kwiatkowski, Roos, Stein, Thomas, & Donald, ; Warton, Meintjes, et al, ; Warton, Taylor, et al, ). These regions underlie learning ability, sensorimotor, and executive function, as well as behavioral and emotional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…One such study by Chang et al (2016) of age, which is intriguing considering that prenatal cigarette smoking exposure has been reported to lead to undesirable outcomes in later life (Müller et al, 2013;Weissman, Warner, Wickramaratne, & Kandel, 1999). One such study by Chang et al (2016) of age, which is intriguing considering that prenatal cigarette smoking exposure has been reported to lead to undesirable outcomes in later life (Müller et al, 2013;Weissman, Warner, Wickramaratne, & Kandel, 1999).…”
Section: Tobacco and Drugs Of Abuse As Prenatal Exposuresmentioning
confidence: 99%
“…Studies with repeated scans are especially informative, partly because some of the observed structural changes may disappear, even if the functional effects of the exposure remain. One such study by Chang et al (2016) examined the effects of prenatal methamphetamine and tobacco exposures, performing repeated scans during the first 6 months of life. Sex-dependent variations in fractional anisotropy (FA) and diffusivity values were seen widely in the corona radiata.…”
Section: Tobacco and Drugs Of Abuse As Prenatal Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…107 After that study prenatal methamphetamine has been associated with reduced regional brain volumes linked to attention processing deficits, 108 altered brain activation patterns (fMRI), 109 and recently alterations in white matter developmental trajectories (DTI). 110 For cocaine-exposed children a variety of gross structural abnormalities were reported in early imaging studies. 106 More recent studies have reported subtle changes, like alterations of regional patterns of striatal morphology in prenatally cocaine-exposed adolescents.…”
Section: Mri Studies Of Prenatally Drug-exposed Childrenmentioning
confidence: 99%